Periodontal Health Status in Adults Exposed to Tobacco Heating System Aerosol and Cigarette Smoke vs. Non-Smokers: A Cross-Sectional Study - Ivana Mišković; Davor Kuiš; Stjepan Špalj; Aleksandar Pupovac; Jelena Prpić (Dentistry Journal, 2024)
Tobacco heating systems (THS) are new products on the market, advertised as a less harmful alternative for smokers, in which tobacco is heated and not burned like in conventional cigarettes. This research explored the effect on periodontal tissues in contact with heating and burning tobacco residual products (smoke and tobacco). Methods: The sample included 66 subjects, patients of the Clinic of Dentistry in Rijeka, Croatia, aged 26–56 (median 38), 64% females. Three age- and gender-matched groups were formed (each N = 22): non-smokers, classic cigarettes smokers and THS smokers. Probing depth (PD) and clinical attachment loss (CAL) were primary research parameters. Results: Three groups differed in average PD and CAL (p ≤ 0.002), with cigarette smokers having the highest and non-smokers the lowest values (p ≤ 0.002). THS consumers generally had lower values of periodontal indices than smokers, but only CAL differed significantly (p = 0.011). Periodontal indices CAL and PD were worse in THS consumers than non-smokers, but they did not reach a level of statistical significance. Cigarette smoking was the only predictor of periodontitis (average CAL ≥ 4 mm) in logistic regression models, with an odds ratio of 4.7 (95% confidence interval 1.2–18.3; p = 0.027). Conclusions: Exposure to nicotine-containing aerosol of THS in adults has a less harmful effect on periodontal tissues, measurable through periodontal indices (PD and CAL), compared to burning tobacco of conventional cigarettes. THS, presented as an alternative product to classic cigarettes, also has a detrimental effect on the periodontium.